Deep Eutectic Solvents - Marcus, Yizhak (Springer International Publishing : Imprint: Springer, 2019)
This is one of the first books fully dedicated to the rapidly advancing and expanding research area of deep eutectic solvents. Written by the internationally recognized expert in solution chemistry, it supplies full information regarding preparation of these new eco-friendly solvents, their properties and applications. The current and potential applications of deep eutectic solvents as organic reaction media, catalytic system, in biomass processing, nanotechnology and metal finishing industry, as well as for extraction and separation are extensively discussed.This highly informative and carefully presented book will appeal to practicing chemists (organic chemists, polymer chemists, biochemists) as well as chemical engineers and environmental scientists.